The effect of sleep quality on academic performance (Annals of Medical Research, 2021)
Aim: Sleep problem is a common issue among children. Insufficient sleep leads to inattention and behavior disorders and thus adversely affects academic performance. In this study, it is aimed to research the effect of sleep quality on the academic performance of eighth-grade students who are going to take the national exam (TEOG) designed for the transition to secondary education from primary education.Material and Methods: Population of the research consists of 272 8th grade students attending eight different schools in Erzincan province. Pittsburgh Sleep Quality Index (PSQI) was applied in research questionnaire and Bodymedia’s Armband Sense Wear Metabolic Holter (SWA) device was utilized to measure sleep effectiveness.Results: It is found that TEOG scores of the students, whose PSQI score 5 and who has a high sleep quality measured by the Bodymedia’s Armband Sense Wear Metabolic Holter, are high.Conclusion: Students who have a good quality of sleep have better academic performance in the school. Body Media Sense Wear Metabolic Holter is an effective and practical method to measure sleep quality.Keywords: Student; sleep quality; PSQI; SWA; academic performance.
Keywords: Student; sleep quality; PSQI; SWA; academic performance.